Anion mediated photophysical behavior in a C60 fullerene [3]rotaxane shuttle - Barendt, T; Rašović, I; Lebedeva, M; Farrow, G; Auty, A; Chekulaev, D; Sazanovich, I; Weinstein, J; Porfyrakis, K; Beer, P (American Chemical Society, 2018)
By addressing the challenge of controlling molecular motion, mechanically interlocked molecular machines are primed for a variety of applications in the field of nanotechnology. Specifically, the designed manipulation of communication pathways between electron donor and acceptor moieties that are strategically integrated into dynamic photoactive rotaxanes and catenanes may lead to efficient artificial photosynthetic devices. In this pursuit, a novel [3]rotaxane molecular shuttle consisting of a four-station bis-naphthalene diimide (NDI) and central C60 fullerene bis-triazolium axle component and two mechanically bonded ferrocenyl-functionalized isophthalamide anion binding site-containing macrocycles is constructed using an anion template synthetic methodology. Dynamic coconformational anion recognition-mediated shuttling, which alters the relative positions of the electron donor and acceptor motifs of the [3]rotaxane’s macrocycle and axle components, is demonstrated initially by 1H NMR spectroscopy. Detailed steady-state and time-resolved UV–vis–IR absorption and emission spectroscopies as well as electrochemical studies are employed to further probe the anion-dependent positional macrocycle–axle station state of the molecular shuttle, revealing a striking on/off switchable emission response induced by anion binding. Specifically, the [3]rotaxane chloride coconformation, where the ferrocenyl-functionalized macrocycles reside at the center of the axle component, precludes electron transfer to NDI, resulting in the switching-on of emission from the NDI fluorophore and concomitant formation of a C60 fullerene-based charge-separated state. By stark contrast, in the absence of chloride as the hexafluorophosphate salt, the ferrocenyl-functionalized macrocycles shuttle to the peripheral NDI axle stations, quenching the NDI emission via formation of a NDI-containing charge-separated state. Such anion-mediated control of the photophysical behavior of a rotaxane through molecular motion is unprecedented.